EXISTENCE OF LOCAL LEGAL PRODUCT NUANCED OF SHARI’AH IN INDONESIA - Patra, Rommy (Yustisia, 2017)
The existence of local legal product  nuanced of shari'a in Indonesia is rampant  in the reform era. The establishment of  local legal product  that nuanced of shari'a is effort to formalize shari'ah  Islam in the life of the nation. But its existence has caused controversy because of have nature of sectarian and vulnerable to violation of human rights such as discriminatory and restrict civil liberties. Therefore, necessary  for the structuring of local legal product  that nuanced of shari'a, if necessary until to cancel it in order to improve the quality of implementation of local autonomy in Indonesia.